Bacteremia due to Dysgonomonas spp: A report of two cases - Almuzara, Marisa (2009)
We report the first documented case of bacteremia caused by a Dysgonomonas species in a patient undergoing hemodialysis and a new case of bacteremia caused by D. capnocytophagoides in a patient with biliary tract infection.